2020
DOI: 10.1038/s41598-020-63148-8
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive immunogenomic landscape analysis of prognosis-related genes in head and neck cancer

Abstract: Head and neck cancer is the sixth most common malignancy around the world, and 90% of cases are squamous cell carcinomas. In this study, we performed a systematic investigation of the immunogenomic landscape to identify prognostic biomarkers for head and neck squamous cell carcinoma (HNSCC). We analyzed the expression profiles of immune-related genes (IRGs) and clinical characteristics by interrogating RNA-seq data from 527 HNSCC patients in the cancer genome atlas (TCGA) dataset, including 41 HPV+ and 486 HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
(50 reference statements)
4
23
0
3
Order By: Relevance
“…Through univariate Cox analysis, we found that 236 IRGs were closely related to the OS of HNSCC patients, indicating that IRGs are very important for the prognosis of HNSCC patients. CCL26, SEMA3G, DKK1, GAST, GNRH1, PDGFA, and ZAP70 genes are related to the OS of HNSCC, which is consistent with the results of Li et al (2020). Analysis of gene function enrichment showed that these prognoses related to immune genes were mainly involved in the interaction of cytokine-cytokine receptor interactions and the nuclear factor (NF)-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Through univariate Cox analysis, we found that 236 IRGs were closely related to the OS of HNSCC patients, indicating that IRGs are very important for the prognosis of HNSCC patients. CCL26, SEMA3G, DKK1, GAST, GNRH1, PDGFA, and ZAP70 genes are related to the OS of HNSCC, which is consistent with the results of Li et al (2020). Analysis of gene function enrichment showed that these prognoses related to immune genes were mainly involved in the interaction of cytokine-cytokine receptor interactions and the nuclear factor (NF)-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 85%
“…In the middle of the last century, Burnt and Thomas proposed the theory of immune surveillance, which suggests that the immune system of the host can recognize precursors of cancer and, in most cases, destroy these precursors before they become clinically apparent (Li et al, 2020). After attack by the innate immune system, tumor antigens (TAs) are released and captured by antigen-presenting cells (APCs) and then processed and loaded onto the major histocompatibility complex (MHC), activating effector T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the researchers revealed a moderate association between the immune checkpoints that contained PD-1, CTLA-4, IDO, and TIGIT and such signature. Li et al [26] used RNA-seq data from 527 head and neck cancer patients from the TCGA database to establish a prognostic prediction model using multivariable Cox regression analysis. Finally, they identi ed a 10-IRG signature including SEMA3G, GNRH1, ZAP70, PLAU, SFTPA2, CCL26, DKK1,…”
Section: Discussionmentioning
confidence: 99%
“… 14 In addition, the researchers revealed a moderate association between the immune checkpoints that contained PD-1, CTLA-4, IDO, and TIGIT and such signature. Li et al, 31 used RNA-seq data from 527 head and neck cancer patients from the TCGA database to establish a prognostic prediction model using multivariable Cox regression analysis. Finally, they identified a 10-IRG signature including SEMA3G, GNRH1, ZAP70, PLAU, SFTPA2, CCL26, DKK1, GAST, PDGFA and STC1.…”
Section: Discussionmentioning
confidence: 99%